Smoking cessation after engagement in HIV care in rural Uganda. Issue 12 (2nd December 2018) - Mitton, Julian A.; North, Crystal M.; Muyanja, Daniel; Okello, Samson; Vořechovská, Dagmar; Kakuhikire, Bernard; Tsai, Alexander C.; Siedner, Mark J.
ABSTRACT: People living with HIV (PLWH) are more likely to smoke compared to HIV-uninfected counterparts, but little is known about smoking behaviors in sub-Saharan Africa. To address this gap in knowledge, we characterized smoking cessation patterns among people living with HIV (PLWH) compared to HIV-uninfected individuals in rural Uganda. PLWH were at least 40 years of age and on antiretroviral therapy for at least three years, and HIV-uninfected individuals were recruited from the clinical catchment area. Our primary outcome of interest was smoking cessation, which was assessed using an adapted WHO STEPS smoking questionnaire. We fit Cox proportional hazards models to compare time to smoking cessation between PLWH pre-care, PLWH in care, and HIV-uninfected individuals. We found that, compared to HIV-uninfected individuals, PLWH in care were less likely to have ever smoked (40% vs. 49%, p = 0.04). The combined sample of 267 ever-smokers had a median age of 56 (IQR 49–68), 56% ( n = 150) were male, and 26% ( n = 70) were current smokers. In time-to-event analyses, HIV-uninfected individuals and PLWH prior to clinic enrollment ceased smoking at similar rates (HR 0.8, 95% CI 0.5–1.2). However, after enrolling in HIV care, PLWH had a hazard of smoking cessation over twice that of HIV-uninfected individuals and three times that of PLWH prior to enrollment (HR 2.4, 95% CI 1.3–4.6, p = 0.005 and HR 3.0, 95% CI 1.6–5.5, p = 0.001, respectively). In summary, we observed high rates of smoking cessation among PLWH after engagement in HIV care in rural Uganda. While we hypothesize that greater access to primary care services and health counseling might contribute, future studies should better investigate the mechanism of this association.